Energy Preservation in Heterogeneous Wireless Sensor Networks through Zone Partitioning - Shahzad Hassan; Muhammad S.Nisar; Hongbo Jiang (Institute of Advanced Engineering and Science, 2016)
Energy preservation is critical task in the wireless sensor networks and the energy cost increases proportionally as the transmission distance increases. Since nodes are equipped with limited energy it is very crucial to decrease the energy consumption by decreasing the communication distance between the nodes. In clustering protocols inter-cluster and intra-cluster communication is most neglected part. We have proposed a new zone based clustering protocol which reduces the intra- clustering and inter-clustering transmission distance between the communicating nodes. Experimental results reveal that our proposed protocols have outperformed the compared protocols in terms of stability period, instability period and throughput.